Konstruksi Pendidikan Islam Muhammadiyah - Kandarisman, Iman (Tsamratul Fikri | Jurnal Studi Islam, 2021)
Islamic education can provide concepts for humans to be able to develop all of their potentials. Because the concept of Islamic education views the human completely, mind and heart, spiritual and physical, morals and skills. Islamic education cannot be separated from the organizing institution. By emphasizing the progressive Islamic character, Muhammadiyah, which has made the education sector as a strategic charity to enlighten the nation, has survived in managing education since its establishment in 1912 until now. The success of Muhammadiyah in developing education cannot be separated from the intelligence of Kiai Ahmad Dahlan, whose thoughts were used as the foundation for establishing Muhammadiyah. Muhammadiyah education is a modern Islamic education that integrates religion with life and between faith and holistic progress. From the womb of Muhammadiyah Islamic education, it is expected that the generation of educated Muslims who have strong faith and personality will be born as well as be able to answer the challenges of the times.